2021
DOI: 10.1051/0004-6361/202039291
|View full text |Cite
|
Sign up to set email alerts
|

CON-quest

Abstract: Context. Some luminous and ultraluminous infrared galaxies (LIRGs and ULIRGs) host extremely compact (r < 100 pc) and dusty nuclei. The high extinction associated with large column densities of gas and dust toward these objects render them hard to detect at many wavelengths. The intense infrared radiation arising from warm dust in these sources can provide a significant fraction of the bolometric luminosity of the galaxy and is prone to excite vibrational levels of molecules such as HCN. This results in emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 75 publications
(110 reference statements)
5
37
0
Order By: Relevance
“…More recent works found that the HCN (3-2) line in its vibrationally excited ν 2 =1 state (HCN-vib) is an excellent tracer of CONs (e.g. Sakamoto et al 2010;Imanishi & Nakanishi 2013;Aalto et al 2015Aalto et al , 2019Falstad et al 2021). In particular, Falstad et al (2021) suggested that a high HCN-vib surface brightness (Σ HCN−vib >1 L pc −2 and/or L HCN−vib /L IR >10 −8 ) indicates that the core may be optically thick up to sub-mm wavelengths (see also e.g.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations

A technique to select the most obscured galaxy nuclei

García-Bernete,
Rigopoulou,
Aalto
et al. 2022
Preprint
Self Cite
“…More recent works found that the HCN (3-2) line in its vibrationally excited ν 2 =1 state (HCN-vib) is an excellent tracer of CONs (e.g. Sakamoto et al 2010;Imanishi & Nakanishi 2013;Aalto et al 2015Aalto et al , 2019Falstad et al 2021). In particular, Falstad et al (2021) suggested that a high HCN-vib surface brightness (Σ HCN−vib >1 L pc −2 and/or L HCN−vib /L IR >10 −8 ) indicates that the core may be optically thick up to sub-mm wavelengths (see also e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sakamoto et al 2010;Imanishi & Nakanishi 2013;Aalto et al 2015Aalto et al , 2019Falstad et al 2021). In particular, Falstad et al (2021) suggested that a high HCN-vib surface brightness (Σ HCN−vib >1 L pc −2 and/or L HCN−vib /L IR >10 −8 ) indicates that the core may be optically thick up to sub-mm wavelengths (see also e.g. Sakamoto et al 2013Sakamoto et al , 2017Scoville et al 2017;Aalto et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations

A technique to select the most obscured galaxy nuclei

García-Bernete,
Rigopoulou,
Aalto
et al. 2022
Preprint
Self Cite